POINTS DE VUE ET PERCEPTIONS D’ADOLESCENTS MAROCAINS SUR L’ALIMENTATION ET L’OBESITE - Khzami, Salah-eddine; Selmaoui, Sabah; Agorram, Boujemaa (European Scientific Journal, ESJ, 2015)
This research aims to identify the representations of pupils about diet and obesity in the outlook for of health education. We have tried to understand the dietary practices through their representations on feeding. Interpretation and discussion of the data could lead to the idea that the viewpoints and perceptions might be connected with social representations. In order to collect data to answer to our problem namely, "what are the perceptions of diet and obesity, how to analyze and to describe them ? " we selected a sample of pupils from private secondary education and another among public school students and we used the questionnaire as a data collection tool. In the practice, paradoxically, young people do not necessarily act in relation to the definitions they give of eating well. The definitions encountered a healthy diet come from common norms in our society. Pupils perceive the food implication in the development certain disease (obesity, diabetes). They consider themselves well informed about the dangers of obesity and consequences of overweight. The results of our research showed that teens surveyed do not seem to be disparaging glances towards obese children.